2014
DOI: 10.3944/aott.2014.13.0029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of platelet-rich plasma on nerve regeneration in a rat model

Abstract: Our experimental study demonstrated positive effects of platelet-rich plasma on nerve regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 21 publications
2
19
0
3
Order By: Relevance
“…They concluded that the functional healing and histological parameters in the PRP group were significantly better than those in the control group. 4 Similar investigations on peripheral nerve injuries have demonstrated the positive effects of PRP on the nerve regeneration and functional recovery. 5 , 20 Takeuchi et al applied a rat organ co-culture system (brain-spinal cord coculture) to evaluate the ability of PRP to promote the axonal growth in spinal cord tissues and identify the growth factors in PRP that contribute to the regulation of the axon growth.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…They concluded that the functional healing and histological parameters in the PRP group were significantly better than those in the control group. 4 Similar investigations on peripheral nerve injuries have demonstrated the positive effects of PRP on the nerve regeneration and functional recovery. 5 , 20 Takeuchi et al applied a rat organ co-culture system (brain-spinal cord coculture) to evaluate the ability of PRP to promote the axonal growth in spinal cord tissues and identify the growth factors in PRP that contribute to the regulation of the axon growth.…”
Section: Discussionmentioning
confidence: 81%
“…Blood platelets contain many different growth and neurotrophic factors that are released when activated, including platelet-derived growth factor (PDGF), transforming growth factor-β (TGF-β), insulin-like growth factor-1 (IGF-1), fibroblast growth factor (FGF), vascular endothelial growth factor (VEGF), brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF) and neurotrophin-3 (NT3). 3 , 4 , 5 There is a great interest in utilizing platelet rich plasma (PRP) in oral and maxillofacial bone grafting procedures, non-healing wounds, ulcers, fistula, skin rejuvenation, and peripheral nerve regeneration. 6 , 7 , 8 , 9 , 10 , 11 , 12 However, there is no literature on the effect of PRP on the regeneration of central nerve fibers, particularly in SCI.…”
Section: Introductionmentioning
confidence: 99%
“…Both recent experimental and clinical studies [11,17] have revealed that intralesional injection of PRP in wound healing and muscle injuries lead to better regeneration, increasing neovascularization, reducing fibrosis and scarring. Previous related studies [35][36][37] had proved that the therapeutic value of PRP in mainly due to high platelet count. Platelets are stimulated by exposure to injured tissues leading to commencement of the coagulation process, which are the onset of the platelets role in healing.…”
Section: Discussionmentioning
confidence: 99%
“…There are a lot of studies evaluating the protective or therapeutic effects of various antioxidants related to the peripheral nerve injury model such as vitamin E, ubiquinone, L-carnitine and agmatine (1,22,33,38) or other substances such as cytidinediphosphocholine, rapamycin, tetanus toxin, platelet-rich plasma, insulin-like growth factor I, dexamethasone and acetyl salicylic acid (5,8,9,12,17,23,29,39), or some energy types such as low level laser irradiation and low-frequency magnetic fields (30,44).…”
Section: █ Discussionmentioning
confidence: 99%